2017
DOI: 10.1007/s00277-017-3094-7
|View full text |Cite
|
Sign up to set email alerts
|

Patients with primary breast and primary female genital tract diffuse large B cell lymphoma have a high frequency of MYD88 and CD79B mutations

Abstract: This study is to retrospectively evaluate the prevalence of MYD88 and CD79B mutations and the clinicopathologic characteristics of patients with primary diffuse large B cell lymphoma (DLBCL) of the female genital tract and breast. The characteristics, treatments, and outcomes of 19 patients diagnosed with primary DLBCL of the female genital tract and breast, who had formalin-fixed and paraffin-embedded tissues obtained from diagnostic samples diagnosed between January 2004 and June 2016, were analyzed retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 18 publications
5
23
0
1
Order By: Relevance
“…We could not classified 16.6% of them. This results are similar to others series of PB-DLBCL [ 10 , 15 , 17 19 ]. The proliferation index, determined by Ki-67 expression, is strikingly high in these samples, higher than or equal to 80% in 16/18 samples.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We could not classified 16.6% of them. This results are similar to others series of PB-DLBCL [ 10 , 15 , 17 19 ]. The proliferation index, determined by Ki-67 expression, is strikingly high in these samples, higher than or equal to 80% in 16/18 samples.…”
Section: Discussionsupporting
confidence: 92%
“…In the last twenty years multiple PBL retrospective clinical studies were published including one randomized clinical trial [ 1 10 , 15 16 ]. However, only two molecular studies, both in oriental population (China and Japan), has been reported [ 10 , 17 ]. The clinical profile of the patients in this series presented a great deal of similarities with previously published ones (clinical presentation, burden of disease, age and response to treatment), with an average age of 66 years [ 1 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both clinical retrospectives and population-based studies report >90% prevalence of stage IE/IIE disease, and 5-year OS of 75–80% [106108]. Clinicopathologic series consistently show predominance of the non-GCB phenotype (60–90%) [109, 107], as well as high prevalence of MYD88 (58–70%) and CD79B (36–40%) mutations [110, 111]. Interestingly, these features resemble testicular lymphoma, and breast lymphomas have recently been also recognized to have a notable predilection for CNS recurrence [107, 108].…”
Section: Prognosis Of Extranodal Dlbcl Arising From Specific Anatomicmentioning
confidence: 99%
“…Similarly, in a series of 6 Chinese patients with DLBCL of the female genital tract, 4 (including 3 uterine/cervical) relapsed in the CNS [113]. Five of the 7 studied uterine lymphomas had the non-GCB phenotype and 4 had the MYD88 L265P mutation [110]. Although confirmatory research is needed, DLBCL of the uterus may be genetically and clinically similar to breast and testicular lymphoma, including the risk of CNS recurrence.…”
Section: Prognosis Of Extranodal Dlbcl Arising From Specific Anatomicmentioning
confidence: 99%